Factors influencing the performance of Agricultural Small and Medium Enterprisesin the Khomas region, Namibia - Kamati, Selma Nakashupi (Graduate School of Business (GSB), 2022)
Small and medium enterprises operating within the agriculture sectors are important entities because of their contribution to the economy. This study's objective was to investigate the factors that influence the performance of agricultural SMEs within the Khomas region. This study adopted the inductive approach in the quest to explore factors which influence the performance of agricultural SMEs in the Khomas region. The study adopted the exploratory design qualitative methods in collecting and analysing data. The population of this study consists of 43 enterprises engaging in agricultural activities on a small-scale basis. Using the convenience sampling method, the researcher identified ten (10) individuals of which seven (7) were farm owners and three (3) were farm managers for participation in the study. The researcher conducted face-to-face interviews with the identified participants using an interview schedule as the data collection tool. The researcher analysed qualitative data through qualitative content analysis. From the analysis, the study concluded that lack of support, lack of formal planning and lack of expertise negatively influence the performance of agriculture SMEs within the Khomas region in Namibia. Financial limitations and the inability of the agricultural SMEs to secure and manage financial resources also have a negative impact on the performance of agricultural SMEs, which leads to their poor performance. The study, however, reveals that agricultural SMEs contribute to economic development through job creation, food production and infrastructure development, and that makes their effective performance significant to the economy. Hence, the study proposes recommendations for the government to provide support to agricultural SMEs, the training of agricultural SMEs to ensure that they have the desired expertise to perform their farming activities, as well as how to manage business operations and create a market for locally produced agricultural products. The study further recommends that agricultural SMEs adopt formal planning to facilitate the effective allocation of resources, as well as track their progress. Implementation of the recommendations would enhance the performance of agricultural SMEs and increase their ability to contribute to economic development.